School Leadership Practices in the Conflict Region of South Thailand - Pattani - Adnan Vateh; Dwi Esti Andriani (Universitas Negeri Yogyakarta, 2021)
This study aims to gain an understanding of the leadership practices of the principals in the conflict region of South Thailand – Pattani. It was a qualitative case study. This study was located at two private Islamic schools in the Yala province, Southern Thailand. Data were collected through interviews and observation. The informants were 14 in total consisting of two principals, two deputy principals, and ten teachers from studied schools. The collected data were analyzed following the interactive model proposed by Miles, Huberman, and Saldana. Audit trail and member checks were used to check the credibility of the data. The results show that building a good relationship with communities and working together to develop a safe environment at school are considered to be important. The principals also motivate students to go to school. In order to make students enjoy studying at school, the principal put a serious effort to provide adequate learning facilities and school infrastructure and to develop the teaching competencies of their teachers. Furthermore, they assure the student parents that it is safe to allow children to go to school.